Tingkat Kelangsungan Penggunaan Kontrasepsi IUD di Klinik Catur Warga PKBI Daerah Bali Tahun 2012 - Astariani, Komang Deri (Community Health)
In the 1970s until the 1990s, IUD is the primary contraceptive method of choice. However, the use of IUD has decreased from year to year. IUD is an effective contraception to be used  in a relative long term. So, it is important to know it the survival of IUD usage and  continuity and the determinants. This study is a retrospective cohort study methods. The sample of this study was 128 IUD acceptors who visit Catur Warga Clinic PKBI Bali March – April 2012. The data were extracted from the medical records and analyzed by using the survival analysis methods. The results of this study showed the IUD continuation rates were 82%, 71% and 44% at 6, 12 and 24 months respectively. The median survival was 26 months. The factor of age (p = 0.301), occupation (p = 0.932), parity (p = 0.607), side effects (p = 0.120), level of education (p = 0.810) and the demand of having a child (p = 0.245) didn’t significantly affect the continuity of IUD use. The survival analysis methods continuation rate of IUD use decrease almost twice after 18 months be used as an alternative statistics test in the analysis of the influence of independent variables with dependent variables which is associated with the time of a certain events. An appropriate method is needed to obtain the corresponding cohort. Information should be provided toward family planning acceptors about the benefit of IUD other longterm contraceptive methods.